2007
DOI: 10.1128/jvi.02679-06
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Autoprocessing of Marek's Disease Herpesvirus Protease Differs from That of Other Herpesviruses

Abstract: Herpesviruses encode a unique serine protease essential for viral capsid maturation. This protease undergoes autoprocessing at two sites, R and M, at the consensus sequence (V, L, I) P3 -X P2 -A P1 /S P1 (where X is a polar amino acid). We observed complete autoprocessing at the R and M sites of Marek's disease virus (MDV) protease following production of the polyprotein in Escherichia coli. Site-directed mutagenesis confirmed the predicted sequence of the R and M sites, with the M site sequence being nonconse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Fuchs et al [ 16 ] observed similar molecular weight multiple banding on immunoblots screened with rabbit anti-sera raised to CyHV-3 ORF149—the target antigen of MAb 10A9. In herpesviruses, protease precursors undergo auto-processing and cleavage in order to achieve cleavage of subsequent polyproteins during capsid maturation and shell assembly [ 44 ], which can also lead to multiple bands being recognised by individual MAbs [ 45 ]. Alternatively, MAbs detecting glycoproteins may also recognise the antigen at multiple molecular weights due to a larger molecule being synthesised following glycosylation and other post-translational modifications resulting in the addition of oligosaccharides, and/or glycosylation intermediates [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fuchs et al [ 16 ] observed similar molecular weight multiple banding on immunoblots screened with rabbit anti-sera raised to CyHV-3 ORF149—the target antigen of MAb 10A9. In herpesviruses, protease precursors undergo auto-processing and cleavage in order to achieve cleavage of subsequent polyproteins during capsid maturation and shell assembly [ 44 ], which can also lead to multiple bands being recognised by individual MAbs [ 45 ]. Alternatively, MAbs detecting glycoproteins may also recognise the antigen at multiple molecular weights due to a larger molecule being synthesised following glycosylation and other post-translational modifications resulting in the addition of oligosaccharides, and/or glycosylation intermediates [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them three were located in the basic region containing the major nuclear localization (NLS) and nucleolar functions (NoLs) and they were thought to affect NLS or NoLs function [15]. The SNPs in the present study could not be compared directly with the previous study because they were present at codons 176, 179, 217, and 266.…”
Section: Discussionmentioning
confidence: 94%
“…On the basis of the four SNPs Korean Meq genes were separated into four alleles-I, II, III, and IV. Although the sample numbers were insufficient, allele II was the prevalent allele, followed by allele I. Alleles III and IV were observed in only one sample each, and the frequencies of each allele should be distinguished from a specific mutation of an individual virus by further studies [15]. 0301-131 and 0301-266 which were originated from 3-week-old chickens in unvaccinated farms were grouped into allele I but others which were from 5-week-old chickens in unvaccinated farms were grouped into other alleles.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations